Genetic Contributions to The Association Between Adult Height and Head and Neck Cancer: A Mendelian Randomization Analysis - Pastorino, Roberta; Puggina, Anna; Carreras-Torres, Robert; Lagiou, Pagona; Holcátová, Ivana; Richiardi, Lorenzo; Kjaerheim, Kristina; Agudo, Antonio; Castellsagué, Xavier; Macfarlane, Tatiana V; Barzan, Luigi; Canova, Cristina; et al. (Scientific reports, 2018)
With the aim to dissect the effect of adult height on head and neck cancer (HNC), we use the Mendelian randomization (MR) approach to test the association between genetic instruments for height and the risk of HNC. 599 single nucleotide polymorphisms (SNPs) were identified as genetic instruments for height, accounting for 16% of the phenotypic variation. Genetic data concerning HNC cases and controls were obtained from a genome-wide association study. Summary statistics for genetic association were used in complementary MR approaches: the weighted genetic risk score (GRS) and the inverse-variance weighted (IVW). MR-Egger regression was used for sensitivity analysis and pleiotropy evaluation. From the GRS analysis, one standard deviation (SD) higher height (6.9 cm; due to genetic predisposition across 599 SNPs) raised the risk for HNC (Odds ratio (OR), 1.14; 95% Confidence Interval (95%CI), 0.99-1.32). The association analyses with potential confounders revealed that the GRS was associated with tobacco smoking (OR = 0.80, 95% CI (0.69-0.93)). MR-Egger regression did not provide evidence of overall directional pleiotropy. Our study indicates that height is potentially associated with HNC risk. However, the reported risk could be underestimated since, at the genetic level, height emerged to be inversely associated with smoking.
Keywords: celogenomová asociační studie; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; tělesná výška; jednonukleotidový polymorfismus; Aged; Female; mendelovská randomizace; senioři; lidé; nádory hlavy a krku; Head and Neck Neoplasms; ženské pohlaví; Male; Mendelian Randomization Analysis; Body Height; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Genome-Wide Association Study; mužské pohlaví